Midthoracic Punctate Midline Myelotomy for Treatment of Chronic, Intractable, Nonmalignant, Abdominal Visceral Pain: 2-Dimensional Operative Video. Issue 2 (13th March 2020) - Ball, Tyler; Aljuboori, Zaid; Nauta, Haring
Abstract: Punctate midline myelotomy (PMM) is a surgical procedure that damages the ascending fibers of the postsynaptic dorsal column (PSDC) pathway to interrupt visceral pain transmission. 1-3 It can offer relief to patients with chronic visceral pain conditions that are refractory to other treatments. Here, we present a surgical video of midthoracic PMM in a patient with chronic, intractable, nonmalignant visceral abdominal pain that failed over a decade of medical treatment. We choose T7-8 as the level for laminectomy in patients with pelvic or lower abdominal pain, because the postsynaptic pain fibers transmitting visceral pain sensation from the lower abdominal organs will invariably be caudal to this level. The patient developed immediate and complete relief of her visceral pain after the procedure, which was sustained through the 11-wk follow-up period to date and was able to be weaned off narcotics. Postoperatively, she remained full strength and had no impairment of light touch or proprioception of her lower extremities. Detailed physical examination showed a reduced vibratory sensation on the glabrous skin of her great toes. Regarding patient-reported sensory changes (not detected on physical examination), she reported some numbness on the insides of her feet that had resolved by 11-wk follow-up. She also reported some numbness of the vulva, but not of the vagina. However, by 11-wk follow-up, she reported this had resolved and she had normal sexual function. The only persistent sensation at 11-wk follow-up was slight tingling in her toes that was not bothersome to her. 4 The patient presented in the following video consented to both the surgical procedure and the publication of her clinical history and operative video.